(untitled) (Al-Academy, 2015)
The diversity of ideas and freedom of expression among the authors, who are looking for what’s new serve the goals of musical expression and aesthetic, which calls for the use of traditional instruments with the formation of the great instrumental music and well-known orchestra, is a major challenge from several quarters, the failure of some of those musical instruments or limited potential or method performed by costly sometimes prevents the use of a permanent in this great configuration, had to be the emergence of some of the problems faced by the author and musician on the one hand and the receiver on the other hand, which must be looking for the perfect, some of these musical instrument are used systematically follows the work of the orchestra is the traditional musical instruments of the Iraqi or say that the popular, were those questions is the difficulties or problems faced by the technical staff starting point for this search.